A heterogeneous composite coating and its preparation method and application
By designing heterogeneous composite coatings, including metal layers with nitrogen-containing gradient changes, composite gradient nitride ceramic layers and nano-multi-layer high-entropy coatings, the problem that existing coatings are difficult to meet multifunctional performance at the same time, achieving high Improved comprehensive performance such as hardness, fracture toughness and thermal stability.
Patent Information
- Application Number
- CN202410643573.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-23
AI Technical Summary
The existing single structural coating is difficult to meet the multifunctional needs of surface hardness, film-based bonding, fracture toughness, thermal stability and high-temperature oxidation resistance of tools, molds and other products at the same time.
Using heterogeneous composite coating structure, including metal layer with nitrogen-containing gradient changes, composite gradient nitride ceramic layer and nano multi-layer high-entropy coating, the interface stress distribution and deformation ability are adjusted through gradient changes and multi-layer structure design, and the interface stress distribution and deformation ability are improved. Comprehensive properties of the coating.
It achieves high hardness, fracture toughness, thermal stability, oxidation resistance and wear resistance, significantly improving the service performance and cutting life of tools, molds and other products.
Smart Images

Figure CN118531349B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a heterogeneous composite coating and a preparation method and application thereof. Background Art
[0002] The current industrial development requires high hardness, film-substrate bonding, fracture toughness, wear and corrosion resistance, as well as excellent thermal stability and high temperature oxidation resistance for surface coatings of products such as cutting tools and molds. However, single-structure coatings (such as AlCrN, AlTiSiN, AlTiN) on the market are difficult to meet the above multi-functional requirements at the same time.
[0003] The hardness, film-substrate bonding, fracture toughness, thermal stability, and antioxidant properties of the coating will affect the service performance of tools, molds, etc. Specifically, if the hardness is low, the wear resistance of the coating is poor; if the film-substrate bonding is low, the coating will peel off; if the fracture toughness is poor, the coating will easily break and fail; if the thermal stability is poor, the coating will easily soften at high temperatures; if the antioxidant property is poor, a loose, brittle oxide layer will easily form on the coating surface, which will easily peel off and fail under the action of external force.
[0004] Patent CN 116411244 A discloses a multi-structure heterogeneous coating and its preparation method and application. The coating includes a TiAlN bottom layer, an AlTiN gradient layer with increasing Al content, an AlTiN / TiSiN nano-multilayer and a TiSiN nano-composite layer connected in sequence, wherein the bottom layer is connected to the substrate; the AlTiN gradient layer with increasing Al content is closely connected to the TiAlN bottom layer; the AlTiN / TiSiN nano-multilayer is a nano-multilayer structure composed of alternating AlTiN and TiSiN layers; the TiSiN layer is a nano-composite structure composed of nanocrystals embedded in an amorphous matrix. The total thickness of the coating is controlled between 1.0 and 6.0 μm. The bonding strength between the multi-structure configuration coating and the substrate is 65 to 120 N, the nano-hardness is 32 to 35 GPa, and the fracture toughness is 5.9 to 10 MPa·m 1 / 2 , with strong toughness and corrosion resistance, and high bonding strength, the cutting life of its coated tool is much longer than that of traditional AlTiN coated tools. The coating provided by the prior art is not good in terms of mold-substrate bonding strength, thermal stability and high temperature oxidation resistance. Therefore, the composition and structure of the existing coating need to be designed and constructed to improve the service performance of the workpiece. Summary of the invention
[0005] The purpose of the present invention is to provide a heterogeneous composite coating and its preparation method and application to solve the problems existing in the above-mentioned prior art. The heterogeneous composite coating includes a bottom layer, an intermediate support layer and a surface functional layer. The bottom layer is a columnar crystal metal layer with a gradient change in nitrogen, the intermediate support layer is a composite gradient nitride ceramic layer with a gradient change in composition and grain size, and the surface functional layer is a nano multilayer high entropy coating.
[0006] One of the technical solutions provided by the present invention:
[0007] A heterogeneous composite coating comprises a metal layer with a nitrogen gradient change, a composite gradient nitride ceramic layer and a nano-multilayer high-entropy coating, wherein the nano-multilayer high-entropy coating is deposited on the composite gradient nitride ceramic layer, the composite gradient nitride ceramic layer is deposited on the metal layer, the metal layer is deposited on the surface of a substrate, the thickness of the metal layer is 0.05-0.5 μm, the thickness of the composite gradient nitride ceramic layer is 0.2-3.0 μm, the thickness of the nano-multilayer high-entropy coating is 1.0-5 μm, and the total thickness of the heterogeneous composite coating is 1-8 μm.
[0008] Preferably, the thickness of the metal layer is 0.2-0.5 μm.
[0009] Preferably, the thickness of the composite gradient nitride ceramic layer is 0.5-2.0 μm.
[0010] Preferably, the thickness of the nano multilayer high entropy coating is 1.0 to 3.0 μm.
[0011] Preferably, the total thickness of the heterogeneous composite coating is 2.0-5.0 μm.
[0012] If the thickness of the heterogeneous composite coating is too large (greater than 7.5 μm), the brittleness of the heterogeneous composite coating will increase, while if the thickness is too small (less than 1.5 μm), the wear resistance and corrosion resistance of the heterogeneous composite coating will be poor.
[0013] Heterogeneous composite coatings are composed of multiple structural coatings, which can overcome the performance defects of single structural coatings and achieve the regulation of comprehensive coating performance. For example, the elastic modulus, hardness and toughness of the metal layer with nitrogen gradient change are between the substrate and the nitride coating, and its own interface hardness and stress show gradient changes, which can coordinate interface deformation and improve the film-substrate bonding and deformation capacity of the coating, but its hardness is low and it is not wear-resistant and corrosion-resistant; although the composite gradient nitride ceramic layer can modulate the interface hardness distribution and improve the coating bonding, its thermophysical properties are greatly different from those of the substrate, which can easily cause stress concentration in the interface and poor coating film-substrate bonding. In addition, the composite gradient nitride ceramic layer is unstable and prone to structural degradation at high temperatures, resulting in a significant reduction in the mechanical properties of the coating; the nano-multilayer high-entropy coating has excellent fracture toughness, but poor interface matching with the substrate and poor film-substrate bonding. Based on the functional characteristics of the above-mentioned layers, the present invention designs a heterogeneous composite structure of a metal layer, a composite gradient nitride ceramic layer and a nano multilayer high entropy coating, which can maximize the effectiveness of each layer and has excellent mechanical properties, corrosion resistance, wear resistance and high temperature performance. Through the above-mentioned multi-structure configuration design and ingenious interlayer interface structure design, a coating with high bonding strength and high toughness is finally prepared, which is conducive to expanding the application field and industrial production scale of the coating.
[0014] Changing the alternating order of the metal layer, the composite gradient nitride ceramic layer and the nano multilayer high entropy coating of the present invention will directly affect the mechanical, physical and chemical properties of the coating, such as hardness, film-substrate bonding strength, fracture toughness, thermal stability and antioxidant properties.
[0015] The second technical solution provided by the present invention is:
[0016] A preparation method for the above-mentioned heterogeneous composite coating comprises the following steps: ultrasonically degreasing, degreasing, cleaning and drying a substrate, using arc ion plating equipment, first using a metal target, combined with argon and nitrogen flow gradient regulation, to deposit a metal layer with a nitrogen gradient change on the surface of the substrate; then using an alloy target, combined with target material current, nitrogen flow gradient control, and substrate negative bias gradient regulation, to deposit a composite gradient nitride ceramic layer on the metal layer; finally, based on a multi-target co-deposition technology, combined with target material composition, nitrogen flow, and substrate negative bias regulation, a nano-multilayer high entropy coating is deposited on the composite gradient nitride ceramic layer to prepare the heterogeneous composite coating.
[0017] Preferably, the specific operation of depositing a metal layer with a nitrogen gradient change on the surface of the substrate is: controlling the metal target, the argon flow rate decreases from 200 sccm to 0 sccm, and the argon flow rate decrease step is 5 to 20 sccm / min; the nitrogen flow rate increases from 0 sccm to 100 sccm, and the nitrogen flow rate increases in steps of 2.5 to 10 sccm / min, the substrate negative bias voltage is 40 to 60 V, the deposition time is 10 to 40 min, the deposition temperature is 400 to 550° C., and the target current is 80 to 160 A.
[0018] Preferably, the metal target is selected from Cr, Ti, CrTi alloy or CrAl alloy.
[0019] Preferably, the specific operation of depositing the composite gradient nitride ceramic layer on the metal layer is: the alloy target current is increased from 80A to 160A, and the current increment step is 0.67-2.67A / min; the nitrogen flow rate is increased from 100sccm to 700sccm, and the nitrogen increment step is 5-20sccm / min; the substrate negative bias voltage is from 40 to 100V, and the step length is 0.5-2.0V / min; the deposition time is 30-120min. The alloy element content and grain size in the prepared composite gradient nitride ceramic layer show gradient changes.
[0020] Preferably, the alloy target is selected from Al70Cr30 alloy target, Al67Ti33 alloy target or AlCrSi alloy target.
[0021] Preferably, the specific operation of depositing the nano multilayer high entropy coating on the composite gradient nitride ceramic layer is: target current is 80-160A, nitrogen flow rate is 300-800sccm, substrate negative bias is 60-100V, deposition time is 60-240min, and deposition temperature is 400-550°C.
[0022] In order to facilitate the adjustment of process parameters, the nitrogen contains carbon-containing gas, preferably acetylene.
[0023] Preferably, the multi-target is a combination target of an AlCr target and a TiSi target, or a combination target of an AlCrB target and a TiSi target. The corresponding composite gradient nitride ceramic layer prepared is Al x Cr 1-x N、Al x Ti 1-x N、Al x (Cr,Si) 1-x N or Al x (Ti,Si) 1-x N coating, where X is the percentage content, ranging from 0 to 1.
[0024] When preparing nano-multilayer high entropy coatings by alloy target regulation, there are at least two alloy targets, and the number of components in each alloy target is at least two.
[0025] More preferably, the nano multilayer high entropy coating includes an A layer and a B layer, which is a multi-component coating composed of an A-rich element (A represents one or more) and a B-rich element (B represents one or more) alternately arranged, and the number of components is at least 5. For example: a nano multilayer structure of an alternating AlCrB-rich AlCrTiSiBN and a TiSi-rich AlCrTiSiBN; or a nano multilayer structure of an AlCr-rich AlCrTiSiCN and a TiSi-rich AlCrTiSiCN, wherein the thickness of the A layer is between 2 and 15 nm, and the thickness of the B layer is between 2 and 15 nm.
[0026] Preferably, the substrate is one or more of cemented carbide, steel material, titanium alloy and aluminum alloy.
[0027] The third technical solution provided by the present invention is:
[0028] An application of the above heterogeneous composite coating in cutting tools and mold products.
[0029] Beneficial effects of the present invention:
[0030] The present invention adopts a metal bottom layer with a nitrogen gradient change, a high-strength and high-toughness gradient layer and a high-temperature wear-resistant nano multilayer high entropy coating, which can effectively solve a series of problems such as hardness, film-substrate bonding, fracture toughness, corrosion resistance, wear resistance and high-temperature performance. By constructing a metal layer with a nitrogen gradient change and a composite gradient nitride ceramic layer with a gradient change in composition and grain size, the interface stress distribution is modulated, the interface deformation is coordinated, and the bonding force between the coating and the substrate, the bearing capacity and the fracture toughness are improved; through the nano multilayer high entropy layer, the coating hardness, fracture heat and high temperature resistance are improved.
[0031] The heterogeneous composite coating provided by the present invention has high hardness, fracture toughness, thermal stability, oxidation resistance and wear resistance, and has broad application prospects in cutting tools, molds and other corrosion-resistant and wear-resistant accessories. The preparation method of the heterogeneous composite coating provided by the present invention has the advantages of low production cost and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0033] Figure 1Schematic diagram of the cross-sectional organizational structure of the heterogeneous composite coating prepared in Example 1-11;
[0034] Figure 2 This is a scanning electron microscope (SEM) image of the cross section of the heterogeneous composite coating prepared in Example 3. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] Example 1
[0041] This embodiment prepares a heterogeneous composite coating, including a metal Cr layer with a nitrogen gradient, an Al x Cr 1-xN gradient layer and AlCrTiSiN nano multilayer structure high entropy layer. The metal Cr layer is connected to the substrate, and the AlCrTiSiN high entropy coating is obtained by alternating deposition of AlCr-rich and TiSi-rich AlCrTiSiN. The specific preparation method is as follows:
[0042] S1. Ultrasonic degreasing, degreasing, cleaning and drying of the cemented carbide substrate;
[0043] S2. Use arc ion plating equipment to prepare a metal Cr layer on a hard surface, control the metal Cr target, and gradually decrease the argon flow rate from 200sccm (starting flow rate) to 0sccm, with a flow rate decrease step of 10sccm / min; increase the nitrogen flow rate from 0sccm (starting flow rate) to 80sccm, with a flow rate increase step of 4sccm / min, a substrate negative bias of 50V, a deposition time of 20min, a deposition temperature of 450℃, and a target current of 160A to obtain a metal Cr layer with a nitrogen content gradient change and a thickness of 0.2μm;
[0044] S3. Control Al 70 Cr 30 alloy target, the target current was adjusted, the current was gradually increased from 80A to 160A, and the current increment step was 1.33A / min; the nitrogen flow rate was gradually increased from 100sccm (starting flow rate) to 500sccm, the nitrogen increment step was 10sccm / min, the substrate negative bias voltage was increased from 50V to 60V, the step size was 0.167V / min, the deposition time was 60min, and the deposition temperature was 450℃, and a composite gradient nitride ceramic layer with gradient changes in composition and grain size was obtained, which was recorded as Al x Cr 1-x N gradient layer, thickness 1.0μm, to obtain the metal Cr layer and Al x Cr 1-x The composite layer of the N gradient layer is denoted as Cr(N)-Al x Cr 1-x N composite layer;
[0045] S4. Based on the multi-target co-deposition technology, AlCr and TiSi targets were used to deposit AlCr-rich and TiSi-rich AlCrTiSiN nano-multilayer high entropy coatings: deposition time 90 min, target current 160 A, deposition temperature 450 ° C, nitrogen flow 600 sccm, substrate negative bias 80 V, and AlCrTiSiN nano-multilayer high entropy coatings with a thickness of 2.0 μm were obtained. Cr(N)-Al x Cr 1-x N-AlCrTiSiN heterogeneous composite coating, the total thickness of the heterogeneous composite coating is 3.2μm.
[0046] Embodiment 2-6
[0047] Embodiments 2-6 provide heterogeneous composite coatings of metal layers of different thicknesses, composite gradient nitride ceramic layers, and nano-multilayer high entropy coatings, wherein the metal layer is connected to the substrate, and the Cr(N)-Al x Cr 1-x A method for preparing a N-AlCrTiSiN heterogeneous composite coating, wherein the AlCrTiSiN high entropy coating is composed of alternating AlCr-rich and TiSiN-rich AlCrTiSiN, comprising the following steps:
[0048] S1. Same as Example 1;
[0049] S2. Use arc ion plating equipment to prepare a metal Cr layer with a nitrogen gradient on the hard surface. The deposition temperature is the same as in Example 1. The other experimental parameters in Examples 2-6 are shown in Table 1 below for the relevant experimental parameters for preparing the metal Cr layer.
[0050] Table 1
[0051]
[0052] S3. Preparation of Al on a Nitrogen Gradient Metal Cr Layer x Cr 1-x N gradient layer, Al is deposited on the surface of the metal Cr layer x Cr 1-x N gradient layer, argon flow rate is 0sccm, and the metal chromium layer and Al x Cr 1-x The composite layer of the N gradient layer is denoted as Cr(N)-Al x Cr 1-x N composite layer, the experimental parameters of Examples 2-6 are shown in Table 2. x Cr 1-x Relevant experimental parameters of N gradient layer.
[0053] Table 2
[0054]
[0055]
[0056] S4. Based on multi-target co-deposition technology, using AlCr target and TiSi target, Cr(N)-Al x Cr 1-x AlCrTiSiN nano multilayer high entropy coating is deposited on the surface of N composite layer to prepare Cr(N)-Al x Cr 1-x N-AlCrTiSiN heterogeneous composite coating, the experimental parameters of Examples 2-6 are shown in Table 3. Relevant experimental parameters for preparing AlCrTiSiN nano-multilayers.
[0057] Table 3
[0058]
[0059] Example 7
[0060] This embodiment prepares a heterogeneous composite coating, including a metal Ti layer containing a nitrogen gradient, an Al x Ti 1-x N gradient layer and AlCrTiSiCN nano multilayer structure high entropy layer, wherein the metal Ti layer is connected to the substrate, the specific preparation method is as follows:
[0061] S1. Ultrasonic degreasing, degreasing, cleaning and drying of the cemented carbide substrate;
[0062] S2. Use arc ion plating equipment to prepare a metal Ti base layer on a hard surface, control the metal Ti target, and gradually decrease the argon flow from 200sccm (starting flow) to 0sccm, with a flow decrease step of 10sccm / min; increase the nitrogen flow from 0sccm (starting flow) to 80sccm, with a flow increase step of 4sccm / min, substrate negative bias 50V, deposition time 20min, deposition temperature 450℃, target current 160A. So far, a metal Ti layer with a gradient nitrogen content is obtained, with a thickness of 0.25μm;
[0063] S3. Control Al 67 Ti 33 alloy target, the target current was adjusted, the current gradually increased from 80A to 160A, and the current increment step was 1.33A / min; the nitrogen flow rate was gradually increased from 100sccm (starting flow rate) to 500sccm, and the nitrogen increment step was 10sccm / min; the substrate negative bias voltage was increased from 50V to 60V, and the step size was 0.167V / min; the deposition time was 60min; the deposition temperature was 450℃; and a composite gradient nitride ceramic layer was obtained, which was recorded as Al x Ti 1-x N gradient layer, thickness 1.0μm, to obtain the metal Ti layer and Al x Ti 1-x The composite layer of the N gradient layer is denoted as Ti(N)-Al x Ti 1-x N composite layer;
[0064] S4. Based on the multi-target co-deposition technology, AlCr and TiSi targets were used, and 20 sccm acetylene gas was introduced to deposit AlCrTiSiCN nano-multilayer high entropy coating: deposition time 90 min, target current 160 A, deposition temperature 450 ° C, nitrogen flow 600 sccm, substrate negative bias 80 V, and AlCrTiSiN nano-multilayer high entropy coating with a thickness of 2.0 μm was obtained. Ti(N)-Al x Ti 1-x N-AlCrTiSiN heterogeneous composite coating, the total thickness of the heterogeneous composite coating is controlled at 3.25μm.
[0065] Example 8
[0066] This embodiment prepares a heterogeneous composite coating, including a metal Cr layer with a nitrogen gradient, an Al x (Cr,Si) 1-x N gradient layer and AlCrTiSiCBN nano multilayer high entropy coating, in which the metal Cr base layer is connected to the substrate, the specific preparation method is as follows:
[0067] S1. Ultrasonic degreasing, degreasing, cleaning and drying of the cemented carbide substrate;
[0068] S2. Use arc ion plating equipment to prepare metal Cr base layer on hard surface, control metal Cr target, argon flow rate gradually decreases from 200sccm (starting flow rate) to 0sccm, flow rate decrease step length is 10sccm / min; nitrogen flow rate increases from 0sccm (starting flow rate) to 80sccm, flow rate increase step length is 4sccm / min, substrate negative bias voltage is 50V, deposition time is 20min, deposition temperature is 450℃, target current is 160A, and a metal Cr layer with nitrogen content gradient change is obtained, with a thickness of 0.2μm;
[0069] S3. Control the AlCrSi alloy target and adjust the target current. The current gradually increases from 80A to 160A, and the current increment step is 1.33A / min. The nitrogen flow rate gradually increases from 100sccm (starting flow rate) to 500sccm, and the nitrogen increment step is 10sccm / min. The substrate negative bias voltage increases from 50V to 60V, and the step size is 0.167V / min. The deposition time is 60min and the deposition temperature is 450℃. The composite gradient nitride ceramic layer is obtained, which is recorded as Al x (Cr,Si) 1-x N gradient layer, thickness 1.0μm, to obtain the metal Cr layer and Al x (Cr,Si) 1-x The composite layer of the N gradient layer is denoted as Cr(N)-Al x (Cr,Si) 1-x N composite layer;
[0070] S4. Based on the multi-target co-deposition technology, AlCrB and TiSi targets were used, and 20 sccm acetylene gas was introduced to deposit AlCrTiSiBCN nano-multilayer high entropy coating: deposition time 90 min, target current 160 A, deposition temperature 450 ° C, nitrogen flow 600 sccm, substrate negative bias 80 V, and AlCrTiSiBCN nano-multilayer high entropy coating with a thickness of 2.0 μm was obtained. Cr(N)-Al x (Cr,Si) 1-x The total thickness of the N-AlCrTiSiBCN heterogeneous composite coating is controlled at 3.25 μm, wherein the AlCrTiSiBCN high entropy layer is composed of alternately deposited AlCrB-rich and TiSi-rich AlCrTiSiBCN layers.
[0071] Example 9
[0072] Same as Example 1, except that the cemented carbide substrate in S1 is replaced with die steel.
[0073] Example 10
[0074] The same as Example 1, except that the cemented carbide substrate in S1 is replaced with titanium alloy.
[0075] Embodiment 11
[0076] The same as Example 1, except that the cemented carbide substrate in S1 is replaced with aluminum alloy.
[0077] Figure 1 Schematic diagram of the cross-sectional organizational structure of the heterogeneous composite coating prepared in Examples 1-11, wherein the gradient layer is denoted as a composite gradient nitride ceramic layer.
[0078] Figure 2 This is a scanning electron microscope (SEM) image of the cross section of the heterogeneous composite coating prepared in Example 3. Figure 2 It can be seen that the heterogeneous composite coating consists of a 0.5 μm Cr(N) metal layer with a nitrogen gradient, and an Al x Cr 1-x N gradient layer and AlCrTiSiN high entropy layer, Al x Cr 1-x The N gradient layer and the AlCrTiSiN high entropy layer are both ceramic layers, which are difficult to be distinguished in SEM, so there is no difference in contrast.
[0079] Comparative Example 1
[0080] This comparative example prepares a metal Cr layer with a nitrogen gradient, and the specific process is as follows:
[0081] S1. Ultrasonic degreasing, degreasing, cleaning and drying of cemented carbide;
[0082] S2. Use arc ion plating equipment to prepare a metal Cr base layer on the hard surface. Control the metal Cr target, and the argon flow rate gradually decreases from 200 sccm (starting flow rate) to 0 sccm, with a flow rate decrease step of 10 sccm / min; the nitrogen flow rate increases from 0 sccm to 80 sccm, with a flow rate increase step of 0.62 sccm / min. The substrate negative bias voltage is 50 V, the deposition time is 320 min, the deposition temperature is 450 ° C, and the target current is 160 A. A metal Cr layer with a gradient nitrogen content is obtained, with a thickness of 3.2 μm.
[0083] Comparative Example 2
[0084] This comparative example prepares a kind of Al2O3 with gradient changes in composition and grain size that is mainstream in the market. x Cr 1-x N gradient layer, the specific process is as follows:
[0085] S1. Ultrasonic degreasing, degreasing, cleaning and drying of cemented carbide;
[0086] S2. Control Al 70 Cr 30 Alloy target, target current was adjusted, the current was gradually increased from 80A to 160A, the current increment step was 1.33A / min; nitrogen flow rate was gradually increased from 100sccm (starting flow rate) to 500sccm, the nitrogen increment step was 10sccm / min; the substrate negative bias voltage was increased from 50V to 60V, the step size was 0.167V / min; deposition time was 195min; deposition temperature was 450℃, and Al with gradient changes in composition and grain size was obtained. x Cr 1-x N gradient layer, thickness is 3.2μm.
[0087] Comparative Example 3
[0088] This comparative example prepares an AlCrTiSiN nano multilayer high entropy coating, and the preparation method thereof comprises the following steps:
[0089] S1. Ultrasonic degreasing, degreasing, cleaning and drying of cemented carbide;
[0090] S2. Based on the multi-target co-deposition technology, AlCrTiSiN nano-multilayer high entropy coating was deposited using AlCr and TiSi targets: deposition time 145min, target current 160A, deposition temperature 450℃, nitrogen flow rate 600sccm, substrate negative bias 80V, to obtain AlCrTiSiN nano-multilayer high entropy coating with a coating thickness of 3.2μm.
[0091] Comparative Example 4
[0092] This comparative example prepares a Cr(N)-Al x Cr 1-x N composite coating, the preparation method thereof comprises the following steps:
[0093] S1. Ultrasonic degreasing, degreasing, cleaning and drying of cemented carbide;
[0094] S2. Use arc ion plating equipment to prepare a metal Cr base layer on the hard surface. Control the metal Cr target, and the argon flow rate gradually decreases from 200 sccm (starting flow rate) to 0 sccm, with a flow rate decrease step of 10 sccm / min; the nitrogen flow rate increases from 0 sccm to 80 sccm, with a flow rate increase step of 0.62 sccm / min. The substrate negative bias voltage is 50 V, the deposition time is 20 min, the deposition temperature is 450 ° C, and the target current is 160 A. A metal Cr base layer with a gradient nitrogen content is obtained, and the thickness of the metal Cr layer is 0.2 μm.
[0095] S3. Control Al 70 Cr 30 Alloy target, target current was adjusted, the current was gradually increased from 80A to 160A, the current increment step was 1.33A / min; nitrogen flow rate was gradually increased from 100sccm (starting flow rate) to 500sccm, the nitrogen increment step was 10sccm / min, the substrate negative bias voltage was increased from 50V to 60V, the step size was 0.167V / min; deposition time was 180min, deposition temperature was 450℃, and Al with gradient changes in composition and grain size was obtained. x Cr 1-x N gradient layer, thickness 3.0μm, to obtain the metal Cr layer and Al x Cr 1-x The composite layer of the N gradient layer is denoted as Cr(N)-Al x Cr 1-x N composite layer, the thickness of which is 3.2 μm.
[0096] Comparative Example 5
[0097] This comparative example prepares a Cr(N)-AlCrTiSiN composite coating, and the preparation method includes the following steps:
[0098] S1. Ultrasonic degreasing, degreasing, cleaning and drying of the cemented carbide substrate;
[0099] S2. Use arc ion plating equipment to prepare metal Cr bottom layer on hard surface, control metal Cr target, argon flow rate gradually decreases from 200sccm (starting flow rate) to 0sccm, and the flow rate decrease step is 10sccm / min; nitrogen flow rate increases from 0sccm (starting flow rate) to 80sccm, and the flow rate increase step is 0.62sccm / min, substrate negative bias voltage is 50V, deposition time is 20min, deposition temperature is 450℃, target current is 160A, and metal Cr bottom layer with nitrogen content gradient change is obtained, with a thickness of 0.2μm;
[0100] S3. Based on the multi-target co-deposition technology, AlCrTiSiN nano-multilayer high entropy coating was deposited using AlCr and TiSi targets: deposition time 120min, target current 160A, deposition temperature 450℃, nitrogen flow rate 600sccm, substrate negative bias 80V, to obtain AlCrTiSiN nano-multilayer high entropy coating with a thickness of 3.0μm, and to obtain Cr(N)-AlCrTiSiN composite coating with a thickness of 3.2μm.
[0101] Comparative Example 6
[0102] This comparative example prepares an Al x Cr 1-x The N-AlCrTiSiN composite coating, the preparation method thereof comprises the following steps:
[0103] S1. Ultrasonic degreasing, degreasing, cleaning and drying of the cemented carbide substrate;
[0104] S2. Control Al 70 Cr 30 Alloy target, target current was adjusted, the current was gradually increased from 80A to 160A, the current increment step was 1.33A / min; nitrogen flow rate was gradually increased from 100sccm (starting flow rate) to 500sccm, the nitrogen increment step was 10sccm / min, the substrate negative bias voltage was increased from 50V to 60V, the step size was 0.167V / min, the deposition time was 60min, the deposition temperature was 450℃, and Al with gradient changes in composition and grain size was obtained. x Cr 1-x N gradient layer, thickness 1.0 μm;
[0105] S3. Based on the multi-target co-deposition technology, AlCrTiSiN nano-multilayer high entropy coating was deposited using AlCr and TiSi targets: deposition time 100min, target current 160A, deposition temperature 450℃, nitrogen flow 600sccm, substrate negative bias 80V, and AlCrTiSiN nano-multilayer high entropy coating with a thickness of 2.2μm was obtained. Al x Cr 1-xN-AlCrTiSiN composite coating, thickness is 3.2μm.
[0106] Comparative Example 7
[0107] Same as Example 1, except that S3 and S4 are swapped to prepare Cr(N)-AlCrTiSiN-Al x Cr 1- x N heterogeneous composite coating.
[0108] Comparative Example 8
[0109] Same as Example 1, except that S3 and S4 are swapped to prepare AlCrTiSiN-Al x Cr 1-x N-Cr(N) heterogeneous composite coating.
[0110] Comparative Example 9
[0111] Same as Example 1, except that steps S3 and S2 are swapped to obtain Al x Cr 1-x N-Cr(N)-AlCrTiSiN heterogeneous composite coating.
[0112] Comparative Example 10
[0113] The same as Example 1, except that the argon gas in step S2 is removed, the nitrogen flow rate is kept constant at 500 sccm, and the other process parameters remain unchanged. x Cr 1-x N-AlCrTiSiN heterogeneous composite coating.
[0114] Comparative Example 11
[0115] The same as comparative example 2, except that the cemented carbide substrate is replaced with die steel.
[0116] Comparative Example 12
[0117] The same as comparative example 2, except that the cemented carbide substrate is replaced with TC4 titanium alloy.
[0118] Comparative Example 13
[0119] The same as comparative example 2, except that the cemented carbide substrate is replaced with high-strength 7015 aluminum alloy.
[0120] Comparative Example 14
[0121] The same as comparative example 3, except that the cemented carbide substrate is replaced with die steel.
[0122] Comparative Example 15
[0123] The same as comparative example 3, except that the cemented carbide substrate is replaced with TC4 titanium alloy.
[0124] Comparative Example 16
[0125] The same as comparative example 3, except that the cemented carbide substrate is replaced with high-strength 7015 aluminum alloy.
[0126] Performance Testing
[0127] Comparative Example 17
[0128] According to Example 1 of a multi-structure heterogeneous coating and its preparation method and application in patent CN116411244 A, a TiAlN-Titanium-containing gradient AlTiN-AlTiN / TiSiN nano-multilayer film-TiSiN nano-composite layer heterogeneous coating was prepared.
[0129] The scratch test method was used to test the bonding strength between the coating and the substrate of Examples 1-11 and Comparative Examples 1-17, and the indentation method was used to test the fracture toughness of the coating of Examples 1-11 and Comparative Examples 1-17. A 1000°C high temperature oxidation experiment for 2h was used in combination with the oxide layer thickness measurement to verify the mechanical friction and wear and high temperature performance of the coating. The test results are shown in Table 4, the performance test results of the heterogeneous composite coatings prepared by Examples 1-17, and Table 5, the performance test results of the coatings of Example 1 and Comparative Examples 1-17;
[0130] Table 4
[0131]
[0132]
[0133] Table 5
[0134]
[0135]
[0136] From Table 4 and Table 5, it can be seen that the bonding force between the coatings of Examples 1-8 of the present invention and the cemented carbide substrate ranges from 78.9 to 120 N, the hardness ranges from 32.9 to 34.2 GPa, and the fracture toughness ranges from 4.5 to 7.8 MPa·m 1 / 2 , the oxide layer thickness range is 0.28-0.61μm. In addition, the bonding strength between the coating and the substrate is related to the hardness of the substrate. The lower the substrate hardness, the worse the coating bonding strength. For example: when the substrate is die steel, titanium alloy and aluminum alloy, the same coating has a film-substrate bonding strength of 86.3N, 56.9N and 40.6N respectively.
[0137] For the comparative examples, when the substrates are all cemented carbides, it is difficult to simultaneously improve the hardness, fracture toughness, film-substrate bonding strength and high-temperature oxidation resistance of the coatings when the coating and substrate are adapted; when the metal base layer is changed to a Cr(N) layer, the film-substrate bonding strength between the coating and the substrate decreases rapidly, and the fracture toughness also decreases; when the substrate is changed to die steel, titanium alloy and aluminum alloy, and the surface coating is a single-configuration Al x Cr 1-x N, the film-substrate bonding strengths are 58.1N, 36.4N and 30.2N respectively; when the surface is a single AlCrTiSiN high-entropy coating, the film-substrate bonding strengths are 53.2N, 33.1N and 29.8N respectively. Since the melting point of aluminum alloy is much lower than 1000℃, the oxidation resistance of the coating on the aluminum alloy surface cannot be measured. In comparison, although the heterogeneous coating in Case 17 has excellent hardness, fracture toughness and film-substrate bonding strength, its oxidation resistance is extremely poor, and the thickness of the oxide layer is 3.1μm.
[0138] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A heterogeneous composite coating, characterized in that: It comprises a metal layer with a nitrogen gradient change, a composite gradient nitride ceramic layer and a nano multilayer high entropy coating; the nano multilayer high entropy coating is deposited on the composite gradient nitride ceramic layer, the composite gradient nitride ceramic layer is deposited on the metal layer, and the metal layer is deposited on the surface of the substrate; The thickness of the metal layer is 0.05-0.5 μm, the thickness of the composite gradient nitride ceramic layer is 0.2-3.0 μm, The thickness of the nano multilayer high entropy coating is 1 to 5 μm, and the total thickness of the heterogeneous composite coating is 1 to 8 μm; The preparation method of the heterogeneous composite coating comprises the following steps: ultrasonically degreasing, degreasing, cleaning and drying the substrate, using arc ion plating equipment, first using a metal target, combined with argon and nitrogen flow gradient regulation, to deposit a metal layer with a nitrogen gradient change on the substrate surface, then using an alloy target, combined with target current, nitrogen flow gradient control and substrate negative bias gradient regulation, to deposit a composite gradient nitride ceramic layer on the metal layer, and finally based on a multi-target co-deposition technology, combined with target composition, nitrogen flow and substrate negative bias regulation, to deposit a nano multilayer high entropy coating on the composite gradient nitride ceramic layer to prepare the heterogeneous composite coating; The specific operation of depositing a metal layer with a nitrogen gradient change on the substrate surface is as follows: controlling the metal target, the argon flow rate decreases from 200 sccm to 0 sccm, the argon flow rate decrease step is 5-20 sccm / min, the nitrogen flow rate increases from 0 sccm to 80 sccm, the nitrogen flow rate increases step is 2.5-10 sccm / min, the substrate negative bias voltage is 40-60V, the deposition time is 10-40min, the deposition temperature is 400-550°C, and the target current is 80-160A; The specific operation of depositing the composite gradient nitride ceramic layer on the metal layer is as follows: the alloy target current is increased from 80A to 160A, the current increment step is 0.67-2.67A / min, the nitrogen flow rate is increased from 100sccm to 700sccm, the nitrogen increment step is 5-20sccm / min, the substrate negative bias voltage is increased from 40V to 60V, the step length is 0.167-2.0V / min, and the deposition time is 30-120min; The specific operation of depositing the nano multilayer high entropy coating on the composite gradient nitride ceramic layer is as follows: the target current is 80-160A, the nitrogen flow rate is 300-800sccm, the substrate negative bias voltage is 60-100V, the deposition time is 60-240min, and the deposition temperature is 400-550°C; The multi-target is a target combined with an AlCr target and a TiSi target, or a target combined with an AlCrB target and a TiSi target; The metal target is selected from Cr, Ti, CrTi alloy or CrAl alloy; The alloy target is selected from Al 70 Cr 30 Alloy target, Al 67 Ti 33 alloy target or AlCrSi alloy target.
2. The heterogeneous composite coating according to claim 1, characterized in that: The substrate is one or more of cemented carbide, steel material, titanium alloy and aluminum alloy.
3. Use of the heterogeneous composite coating according to claim 1 in cutting tools and mold products.
Citation Information
Patent Citations
Multilayer multi-component compound hard PVD (Physical Vapor Deposition) plating layer on surface of piston ring, piston ring and preparation process
CN103789725A